Kampus Merdeka Membentuk Generasi Unggul Menuju Tantangan Masa Depan - Nursita Aulia; Masduki Asbari; Renawati (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this program is to improve the quality of human resources (HR) by providing various internship opportunities, independent research, student exchanges and educational programs for students. By involving more than 160 companies and organizations, including state-owned enterprises, the program has created more than 20,000 open positions for students in various programs, proving significant industry participation. The result is an increase in student engagement and participation in various activities outside of school, resulting in graduates who are ready to face global challenges. In conclusion, the Merdeka Campus program has marked a paradigm shift in higher education in Indonesia towards an inclusive, adaptive, and globally competitive direction.